Endoparásitos con potencial zoonótico en cinco especies de peces de consumo comercializados en el puerto "Don José" - Iquitos - Selis Pinchi, Liliana Esther (2022)
The objective of the present study was to identify the species of endoparasites with zoonotic potential in five species of commercialized fish in the “Don José” port: Plagioscion squamosissimus (Heckel, 1840), Pseudoplatystoma punctifer (Castelnau, 1855); Pseudoplatystoma tigrinum (Valenciennes, 1840); Cichla monoculus (Spix & Agassiz, 1831) and Hypophthalmus edentatus (Spix & Agassiz, 1829). The specific objectives were: to describe the main morphological characteristics, to record the place of fixation and to calculate the main parasitic indices. The study was conducted at the Laboratory of Parasitology and Aquaculture Health of the Research Institute of the Peruvian Amazon (IIAP). A total of 150 fish (30 per species) were used, which were analyzed trying to find endoparasites present in muscles and internal organs,The results of the fish analysis led to the taxonomic identification of three zoonotic nematodes: Anisakis sp, Contracaecum sp and Eustrongylides sp and two non-zoonotic species: Procamallanus (Spirocamallanus) inopinatus and Cucullanus pseudoplatystomae. These parasites were found infecting; muscles, liver, stomach, swim bladder and intestine, the latter being the organ with the highest percentage of infection. This work evidences the presence of parasites with zoonotic potential in fish obtained from the "Don José".